Barocaloric effect in neopentylglycol plastic crystal: A theoretical study. (1st March 2023) - de Oliveira, N.A.
Abstract: In this paper, we theoretically discuss the entropy changes and the barocaloric effect in neopentylglycol plastic crystal. For this purpose, we use a microscopical model Hamiltonian in which are included the rotational and vibrational motions of the molecules in the lattice. The theoretically calculated isobaric entropy and the barocaloric quantities Δ S i s o and Δ T a d are in reasonable agreement with the experimental observations. Graphical abstract: